Globalization and popular sovereignty [ democracy's transnational dilemma - Lupel, Adam (Rethinking globalizations, 2009)
Analyzes the impact of globalization on the concept of popular sovereignty and rethinks it for the transnational domain. This book explores how popular sovereignty has determined the form of democratic citizenship and how democratic citizenship and legitimacy can be conceived in the transnational sphere in the absence of a global sovereign order